Assessment of Biological Remediation of Polychlorinated Biphenyls (PCB) in the Environment by Microorganisms and Plants - R. O. Anyasi; H. I. Atagana (Research Aspects in Biological Science Vol. 3, 2022)
Polychlorinated biphenyls (PCBs) are one of the persistent organic pollutants (POPs) used worldwide between the 1930 and 1980s. Many PCBs can still be found in the environment such as in soils and sediments, even though their use has been heavily restricted. This review summarizes the most frequent remediation solutions including, phytoremediation, microbial degradation, dehalogenation by chemical reagent, and PCBs removal by activated carbon. New insights that emerged from recent studies of PCB remediation including supercritical water oxidation, ultrasonic radiation, bimetallic systems, nanoscale zero-valent iron based reductive dehalogenation and biofilm covered activated carbon, electrokinetic remediation, and nZVI particles in combination with a second metal are overviewed. . Despite the different steps adopted to reduce its presence, the widespread distribution of this substance and other persistent organic pollutants (POPs) that have common chemical, toxicological, and environmental features continues to rise in the environment. This review focuses on potential trends in PCB remediation in the environment, as well as the approaches used. Plant remediation and microorganism degradation as biological detoxification agents of the chemical are also compared. This will highlight potential bioremediation enhancement techniques involving the use of plants and microorganisms, thereby filling the gap left by traditional remediation procedures, which have their own limitations and drawbacks.